High- voltage pulsed current (HVPC) electrical stimulation for treatment of diabetic foot ulcer (DFU) - a review - MUKESH KUMAR SINHA MPT; KOVELA RAKESH KRISHNA MPT; DHANESH KUMAR K U, PT, Ph.D (International Journal of Pharma and Bio Sciences, 2017)
Diabetes is a group of Metabolic Syndrome either because of insufficient insulin production or decreased response of body’s cells to insulin or both. The sensory, motor and autonomic dysfunctions are comm.only noted in Persons with Diabetes. Specifically blood flow will be altered because of the autonomic dysfunction following diabetes. This is the reason a diabetic individual has a risk of developing a diabetic foot ulcer (DFU), which leads to limb amputation. Apart from regular medical management, Physical Therapy treatment specially electrotherapy modalities has gained crucial importance in the management of DFU. Among those the contribution of High Voltage Pulsed Current ( HVPC) is noteworthy. HVPC is a monophasic pulsed electric current that improves blood flow and capillary density. This review is carried out to examine whether the clinical use of HVPC is beneficial for healing of Diabetic foot ulcer. An electronic search was done in CINAHL, OVID, PubMed, Pro Quest, Science Direct, Ind Med, & Google Scholar from 1970 to 2016 that used HVPC as a electrical stimulation for diabetic foot ulcer treatment. Quality of the article was assessed by quality index score which consists of five domains with a highest score of 32. HVPC has been appears to be one of the best adjunctive therapy that is underutilized in the area of treatment of diabetic foot ulcer.